Modern Questions of Celestial Mechanics - Colombo, Giovanni; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
C. Agostinelli: Sul problema delle aurore boreali e il moto di un corpuscolo elettrizzato in presenza di un dipolo magnetico.- G. Colombo: Introduction to the theory of earth$1 (Bs motion about its center of mass.- E.M. Gaposchkin: The motion of the pole and the earth$1 (Bs elasticity as studied from the gravity field of the earth by means of artificial earth satellites.- I.I. Shapiro: Radar astronomy, general relativity, and celestial mechanics.- V. Szebehely: Applications of the restricted problem of three bodies in space research.- G.A. Wilkins: The analysis of the observation of the satellites of Mars.s
C. Agostinelli: Sul problema delle aurore boreali e il moto di un corpuscolo elettrizzato in presenza di un dipolo magnetico -- G. Colombo: Introduction to the theory of earth$1 (Bs motion about its center of mass -- E.M. Gaposchkin: The motion of the pole and the earth$1 (Bs elasticity as studied from the gravity field of the earth by means of artificial earth satellites -- I.I. Shapiro: Radar astronomy, general relativity, and celestial mechanics -- V. Szebehely: Applications of the restricted problem of three bodies in space research -- G.A. Wilkins: The analysis of the observation of the satellites of Mars.s
Keywords: Mathematics; Differential equations, partial; Mechanics; Astronomy; Mathematics; Partial Differential Equations; Mechanics; Astronomy, Astrophysics and Cosmology